Diversity of Phytoplankton and Zooplankton in Songkhla Lake - Ramarn, Tueanta; Chusong, Jaruwan; Amornviyachai, Witjittra; Chonongbua, Preeyalak (Burapha Science Journal, 2026)
Diversity of phytoplankton and zooplankton in Songkhla Lagoon were studied at four stations, namely Koh Yai, Ban Chongfuun, Ban Mai and Khuan Niang. Samples were collected twice in December 2020 and February 2021. Water quality during the study period in all four areas is in normal condition. The results showed that phytoplankton were found in 3 divisions, 6 classes, 17 orders, 29 families, 40 genera, with phytoplankton in Division Chlorophyta being the dominant group, followed by Division Chromophyta. While zooplankton is found in 7 Phylum, 6 Classes, 8 Orders, 18 Family, 22 Genera. The dominant group is zooplankton in Phylum Arthropoda, followed by Phylum Rotifera. Spatial variation was found. The predominant group of phytoplankton in the Koh Yai and Ban Chong Phuen is Division Chlorophyta. In Ban Mai and Ban Khok Mueang, the predominant group of phytoplankton is found in two divisions, Division Chlorophyta and Division Chromophyta. The predominant group in Koh Yai, Ban Chong Fuen and Ban Mai were Phylum Arthropoda. The most common zooplankton in Ban Khok Mueang Station were Phylum Rotifera, followed by Phylum Protozoa. Temporal variation was observed as well. In December 2020, zooplankton was found in Phylum Rotifera as the predominant group. On the other hand, Phylum Arthropoda was the dominant phylum in February.